Duration of post-operative hypocortisolism predicts sustained remission after pituitary surgery for Cushing's disease. Issue 8 (November 2017) - Bansal, Prachi; Lila, Anurag; Goroshi, Manjunath; Jadhav, Swati; Lomte, Nilesh; Thakkar, Kunal; Goel, Atul; Shah, Abhidha; Sankhe, Shilpa; Goel, Naina; Jaguste, Neelam; Bandgar, Tushar; et al.
Abstract : Purpose: Transsphenoidal surgery (TSS) is the primary treatment modality for Cushing's disease (CD). However, the predictors of post-operative remission and recurrence remain debatable. Thus, we studied the post-operative remission and long-term recurrence rates, as well as their respective predictive factors. Methods: A retrospective analysis of case records of 230 CD patients who underwent primary microscopic TSS at our tertiary care referral centre between 1987 and 2015 was undertaken. Demographic features, pre- and post-operative hormonal values, MRI findings, histopathological features and follow-up data were recorded. Remission and recurrence rates as well as their respective predictive factors were studied. Results: Overall, the post-operative remission rate was 65.6% (early remission 46%; delayed remission 19.6%), while the recurrence rate was 41% at mean follow-up of 74 ± 61.1 months (12–270 months). Significantly higher early remission rates were observed in patients with microadenoma vs macroadenoma (51.7% vs 30.6%, P  = 0.005) and those with unequivocal vs equivocal MRI for microadenoma (55.8% vs 38.5%, P  = 0.007). Patients with invasive macroadenoma had poorer (4.5% vs 45%, P  = 0.001) remission rates. Recurrence rates were higher in patients with delayed remission than those with early remission (61.5% vs 30.8%, P  = 0.001). Duration of post-operative hypocortisolemia ≥13 months predicted sustained remission with 100% specificity and 46.4% sensitivity. Recurrence could be detected significantly earlier (27.7 vs 69.2 months, P  < 0.001) in patients with available serial follow-up biochemistry as compared to those with infrequent follow-up after remission. Conclusion: In our study, remission and recurrence rates were similar to that of reported literature, but proportion of delayed remission was relatively higher. Negative/equivocal MRI findings and presence of macroadenoma, especially those with cavernous sinus invasion were predictors of poor remission rates. In addition to early remission, longer duration of post-operative hypocortisolism is an important predictor of sustained remission. Regular biochemical surveillance may help in identifying recurrence early.